2019
DOI: 10.3390/resources8010020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 3D-Printing Technologies on the Transformation of Industrial Production in the Arctic Zone

Abstract: Today the process of transition to a new technological order has become evident to everyone, especially in developed countries. One of the most urgent areas for ensuring the long-term competitiveness of industrial enterprises is the development of the Arctic zone. This region has many economic and logistical difficulties, the solution of which may lie in the use of advanced technologies of the new technological order, for example, 3D-printing technologies. The aim of the article is to study the transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A lot of activities are streamlined by combining designs, consulting, sales, and production in one location and converting the warehouse into a small lab. The research by Evgeni et al [68] discovered that the main cost components, such as manufacturing costs and the details of (related) SC costs, are greatly reduced when TM is replaced with AM technology. This allowed for more flexible and efficient product design.…”
Section: Time Cost Inventory and Operations Efficiency-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of activities are streamlined by combining designs, consulting, sales, and production in one location and converting the warehouse into a small lab. The research by Evgeni et al [68] discovered that the main cost components, such as manufacturing costs and the details of (related) SC costs, are greatly reduced when TM is replaced with AM technology. This allowed for more flexible and efficient product design.…”
Section: Time Cost Inventory and Operations Efficiency-related Factorsmentioning
confidence: 99%
“…The study by Zhen [81] used the system dynamic approach to create an international SC model, and the results showed that employing 3D printing will greatly minimize the amount of transportation and bring industrial activities closer together. According to Evgenii et al [68], AM can decrease the number of raw materials used in the SC and eliminate the need for energy-intensive, inefficient, and environmentally damaging manufacturing methods. The study by Inigo et al [69] implied that AM technologies introduce new opportunities to change a product's architecture at any stage of product development while compressing the SC and enabling quick responses to changing customer demands.…”
Section: Resource Energy Pollution and Waste-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the work of scientists in the field of stimulating the innovative activity of scientists, it is worth noting that there are many in-depth researches of material incentives [6][7][8][9][10][11][12][13][14][15][16][17], however, the relationship between the results of innovative activity and the mechanisms for stimulating innovative activity of university employees has not been adequately research.…”
Section: Introductionmentioning
confidence: 99%
“…The matters related to investing in digitalization are considered [15,16,17]. It is noted that investing in the sphere of innovative development has a more significant effect on the GPD of the developed countries in comparison to the developing ones.…”
Section: Introductionmentioning
confidence: 99%